Nanostructure investigation of particle emission by using TEM image processing method - Karin, Preechar; Songsaengchan, Yutthana; Laosuwan, Songtam; Charoenphonphanich, Chinda; Chollacoop, Nuwong; Katsunori, Hanamura (My University, 2013)
Particulate matters (PMs) must be removed from the exhaust gas emitted from engines to protect the environment and human health. The problem of particulate emissions from diesel engine can be reduced in many ways, for examples: development of modern engine, fuel additives, diesel particulate filter (DPF) and oxygenated fuel. This paper describes a part of an ongoing research project in PM reduction as emitted from combustion. The main part is study of PM nanostructure by using Transmission Electron Microscopy (TEM). The primary size distributions as well as PM structures were presented by TEM images. The average primary sizes of biodiesel and diesel fuels PMs are approximately 30-40 nm and 50-60 nm, respectively. The average carbon platelet sizes of both PMs are in the range of 0.1-7.0 nm. Moreover, approximately 830 carbon atoms per cubic nanometer of PMs also could be estimated and presented in the present report. The results of this research would be used as basic information for design and develop removing process of PM emitted from engine combustion which using in diesel and biodiesel fuels. © 2013 The Authors.
Keywords: Engine; Particulate Filter; Particulate Matter; Transmission Electron Microscopy